2014
DOI: 10.3746/pnf.2014.19.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baechu Kimchi Added Ecklonia cava Extracts on High Glucose-induced Oxidative Stress in Human Umbilical Vein Endothelial Cells

Abstract: Endothelial cell dysfunction is considered to be a major cause of vascular complications in diabetes. In the present study, we investigated the protective effect of a baechu kimchi added Ecklonia cava extract (BKE) against high glucose induced oxidative damage in human umbilical vein endothelial cells (HUVECs). Treatment with a high concentration of glucose (30 mM) induced cytotoxicity, whereas treatment with BKE protected HUVECs from high glucose induced damage; by restoring cell viability. In addition, BKE r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, Min and Han [ 13 ] reported that Polyopes lancifolia extract protected HUVECs from high glucose-induced damage. Another study has reported that baechu kimchi added Ecklonia cava extract protected HUVECs from high glucose-induced damage by increasing cell viability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Min and Han [ 13 ] reported that Polyopes lancifolia extract protected HUVECs from high glucose-induced damage. Another study has reported that baechu kimchi added Ecklonia cava extract protected HUVECs from high glucose-induced damage by increasing cell viability [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent studies on the correlation between antioxidant transcription factors and COVID-19 found that the intake of kimchi, a representative Korean fermented dish, could alleviate COVID-19 symptoms by activating nuclear factor-erythroid 2-related factor-2 [ 3 , 4 ]. Other health benefits of kimchi, such as anticancer, anti-obesity, anti-diabetes, and antioxidant effects, have also been well established, and are closely associated with lactic acid bacteria (LAB) and LAB-derived bioactive substances [ 5 - 11 ].…”
Section: Introductionmentioning
confidence: 99%